Tuberculous Osteopathy: A Case Report - M. MAZAHER; S. MOHAMEDl; S. SHARIAT (Acta Medica Iranica, 1971)
A rare case of tuberculosis of many bones (skull, ribs and pubis) is described. There was also paravertebral cold abscess with fistulisation opened to groin region; no lesions were seen in lungs, urinary or gastrointestinal tracts. The response to medical treatment was favourable.